Generalized Quasilinearization for the System of Fractional Differential Equations - Peiguang Wang; Ying Hou (Journal of Function Spaces and Applications)
This paper considers the initial value problems of the system of fractional differential equations and constructs two monotone sequences of upper and lower solutions. By using quasilinearization technique, monotone sequences of approximate solutions that converge quadratically to a solution are obtained.